Study on entrepreneurship competencies of coffee farmers - Timbul Rasoki; Ana Nurmalia; Lina Asnamawati (Agriekonomika, 2022)
Coffee is the main source of income for 1.8 million heads of farming families spread across almost all provinces and 69 thousand families of employees of large plantations, plays a role in job creation, encouraging domestic agribusiness. The stock of coffee beans in Indonesia for the last 5 years has continued to decline. Seeing this phenomenon, researchers are interested in studying entrepreneurial competence, and the factors that influence it both directly and indirectly. Determination of respondents using the method of arikunto 10% of the total population, then obtained as many as 496 respondents. Analysis of research data using path equations. The results of the study stated the eleven indicators of entrepreneurial competence have competencies of which 1 indicator is included in low competence. The results of the path analysis state that X2 (Farming Business Experience), X5 (Access to Information), X7 (Farmers' Perceptions of Government Policy) have a significant direct and indirect influence on the entrepreneurial competence of farmers.